Income Growth, Inequality and Poverty Reduction : A Case Study of Eight Provinces in China - Goh, Chor-ching (2012)
This paper examines the growth performance and income inequality in eight Chinese provinces during the period of 1989-2004 using the China Health and Nutrition Survey data. It shows that income grew for all segments of the population, and as a result, poverty incidence has fallen. However, income growth has been uneven, most rapidly in coastal areas, and among the educated. A decomposition analysis based on household income determination suggests that income growth can largely be attributed to the increase in returns to education and to the shift of employment into secondary and tertiary sectors.